Pharmacology of HIV Cure: Site of Action. Issue 4 (5th March 2021) - Devanathan, Aaron S.; Cottrell, Mackenzie L.
Abstract : Despite significant advances in HIV treatment over the past 30 years, critical barriers to an HIV cure persist. The HIV reservoir, defined at both the cellular and anatomical level, constitutes the main barrier to cure. While the mechanisms underlying the reservoir are not yet well understood, one theory to explain persistence at the anatomical level is that subtherapeutic exposure to antiretroviral therapy (ART) within certain tissue compartments permits ongoing replication. Characterizing ART pharmacology throughout the body is important in the context of these potential pharmacologic sanctuaries and for maximizing the probability of success with forthcoming cure strategies that rely on latency reversal and require ART to prevent reseeding the reservoir. In this review, we provide a comprehensive overview of ART and latency reversal agent distribution at the site of action for HIV cure (i.e., anatomical sites commonly associated with HIV persistence, such as lymphoid organs and the central nervous system). We also discuss methodologic approaches that provide insight into HIV cure pharmacology, including experimental design and advances within the computational, pharmaceutical, and analytical chemistry fields. The information discussed in this review will assist in streamlining the development of investigational cure strategies by providing a roadmap to ensure therapeutic exposure within the site of action for HIV cure.